Endovascular Stent Thrombectomy in Patients With Acute Lower Limb Arterial Thrombosis on the Background of COVID-19 - I. S. Semyin; A. N. Ivanenko; A. S. Zharova; V. A. Pyatkov; I. L. Bakhtin; G. A. Sobolev; A. D. Kiselev; A. V. Korotkikh; A. N Kazantsev; K. P. Chernykh (Неотложная медицинская помощь)
AIM Analysis of the outcomes of endovascular stent thrombectomy in patients with acute arterial thrombosis of the lower extremities on the background of COVID-19.MATERIAL AND METHODS This retrospective study for the period from January 1, 2020 to March 1, 2022 included 34 patients with acute lower limb ischemia who were diagnosed with the novel coronavirus infection SARS-COV-2. Endovascular stent thrombectomy was performed according to the standard technique using a Destination 8F guiding sheath (Terumo), an Advantage 0.014`` guidewire (Terumo), and a Casper stent (Microvention, Terumo) as a stent retriever. In case of fragmentation of thrombotic masses in the guide sheath, manual aspiration of thrombi was performed using a standard 50,0 ml syringe. Self-expanding nitinol stents were implanted in 11 clinical cases.RESULTS Intraoperative bleeding from the puncture site of the artery developed in 14.7% of cases, which required additional manipulation to achieve hemostasis. Every tenth (11.8%) patient developed myocardial infarction, in 2.9% of cases — ischemic stroke. In the hospital postoperative period during the first hours after surgery, 26.5% of patients developed rethrombosis which required re-intervention. In 8.8% of cases, retrombectomy was unsuccessful, and limb amputation was performed. A fatal outcome occurred in 67.6% of cases, which was due to an increase in multiple organ failure and the development of sepsis.CONCLUSION Endovascular stent thrombectomy is characterized by a low risk of rethrombosis and amputation in the context of COVID-19.